PERKEMBANGAN TARI PIRING GELAS DARI TAHUN 2002 HINGGA 2013 DI KECAMATAN KARANG JAYA SUMATRA SELATAN - Dibba Gazwami; Indrayuda Indrayuda; Darmawati Darmawati (FBS Universitas Negeri Padang, 2015)
Abstract This study was conducted due to the fact that there had been a great development of Piring Gelas dance from 2002 to 2013. In 2002, this kind of dance was only found in desa Embacang. Leter, in the area of 2013, it could not only be foun in this village, but also could be foun in outside Desa Embacang. For this reason, Desa Embacang was known as the place of origin of this Piring Gelas dance. In the period of 2002-2003, there was also a development of this dance in the frequency of this dane show. This study aimed at observing the development of Piring Gelas This study was aqualitative study with a descriptive method. The data were taked from the literature study, obsservation interview, and documentation. Moreover the data were analiyzed qualitatively with the procedures of: data classification, data reduction, data presentation, data collection, dan data verification. The result of this study showed that there was massiv development of this Piring Gelas dance qualititatively in wich there was an expancion of area in wich this dance was shown as well as the increasing number of frequency of showing this dance in the sociality. The development of the dance could be seen periodically. In the period of 2002-2004, the dance of piring gelas developed in area of Desa Embacang Baru with quite a little improvement. In the period of 2005-2009, this dance was not only developed in Desa Embacang Baru and Embacang Lama, but also it could be found in other places such as Desa Karang Dapo, and Muara Rupit. In this case, the frequency of this dance show was also increased. This dance was regulary shown in almost all ivents in the society. Moreover, in the period of 2010-2013, Piring Gelas dance was frequently shown in all events in several areas outside South Sumatra. Keywords: Piring Gelas Dance, Development of Piring Gelas Dance.